Ammonium as a signal for physiological and morphological responses in plants - Liu, Ying; von Wirén, Nicolaus (Journal of experimental botany, 2017)
Ammonium is a major inorganic nitrogen source for plants. At low external supplies, ammonium promotes plant growth, while at high external supplies it causes toxicity. Ammonium triggers rapid changes in cytosolic pH, in gene expression, and in post-translational modifications of proteins, leading to apoplastic acidification, co-ordinated ammonium uptake, enhanced ammonium assimilation, altered oxidative and phytohormonal status, and reshaped root system architecture. Some of these responses are dependent on AMT-type ammonium transporters and are not linked to a nutritional effect, indicating that ammonium is perceived as a signaling molecule by plant cells. This review summarizes current knowledge of ammonium-triggered physiological and morphological responses and highlights existing and putative mechanisms mediating ammonium signaling and sensing events in plants. We put forward the hypothesis that sensing of ammonium takes place at multiple steps along its transport, storage, and assimilation pathways.